Impact of interpregnancy interval on maternal and perinatal outcomes - Jani, Heta T.; Sud, Shalini; Jeyaseelan, Shanti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Inter-pregnancy interval (IPI) refers to the duration between the birth of one baby and the conception of the next pregnancy. In developing countries, a short inter-pregnancy interval (SIPI) poses a significant challenge, leading to higher risks of maternal and neonatal mortality. Aim was to determine the impact of SIPI on maternal and perinatal outcomes. Methods: This prospective observational comparative study was carried out from October 2020 to May 2022. Non-probability convenient sampling was used, and the minimum sample size was calculated to be 140. Primigravida, multiple gestations, molar pregnancies, and those with major complications were excluded. The study compared two groups: cases (70 women with IPI ≤18 months) and controls (70 women with IPI between ≥19 months to ≤59 months). A p value <0.05 was considered statistically significant. Results: Higher proportion of younger mothers had lower IPI as compared to those who were older. Higher proportion of mothers with short IPI had anaemia (p value- 0.017) while lower proportion had pregnancy induced hypertension (PIH) (p value- 0.001). On logistic regression analysis, patients with SIPI had lesser risk of PIH (p value- 0.036, OR: 0.266), higher risk of obstetric cholestasis (p value- 0.006, OR: 4.186) and higher risk of scar dehiscence/tenderness (p value- 0.003, OR: 10.666). Conclusions: Mothers with a short interpregnancy interval of 18 months or less experienced significant morbidity and adverse perinatal outcomes, such as scar dehiscence and obstetric cholestasis. However, the incidence of pregnancy-induced hypertension (PIH) was notably lower in this group.